Persistent and adaptive power system for solar powered sensors of Internet of Things (IoT) - Sahraei, Nasim; Watson, Sterling; Sofia, Sarah; Pennes, Anthony; Buonassisi, Tonio; Peters, Ian Marius (Energy Procedia, 2017)
Powering remote sensors with real-time communication persistently is a key enabling challenge for the internet of things (IoT). Energy harvesting from the environment, energy storage, and power consumption of such sensors need to be jointly considered and duly optimized for the technology to move toward power autonomy and miniaturization. Using photovoltaic (PV) technology, the sun can provide enough power for devices operating outdoors to ensure persistent operation over years without the need to ever access them. High efficiency solar cells feature high power generation densities that utilize the ever present solar power in outdoor environments. The main challenge in designing PV powered devices for predictable operation is The intermittent nature of the solar resource is: the PV panel needs to be combined with energy storage, and the whole device must be designed and optimized specifically for persistent operation outdoors. As presented in our previous work [1], the design must consider (i) the changes (daily, seasonal, and due to cloud cover) in the solar insolation, (ii) the solar cell characteristics, and (iii) the power requirement of the sensing and communicating module. From these characteristics, we estimate the necessary storage capacity to reliably power the device over several years. The system size is then optimized for minimum cost or volume. In this paper, we present how an adaptive power consumption pattern affects the dimensions of solar cell and battery, and the optimal cost of the system. In our design approach, we constrain the design of the adaptive power system based on the available power as well as the expected system performance, using the rate of acquired data from the sensor as a measure of performance. This means the performance - or the power consumption profile - changes based on availability of energy source. We consider different scenarios in which the performance is adapted to the remaining storage and to the recent solar insolation, and discuss the design parameters and constraints in each scenario.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Internet of Things (IoT); photovoltaics (PV); power autonomouse; power system sizing; smart sensor; soalr powered sensors; system design